Modeling Untreated Wastewater Evolution and Swimmer Illness for Four Wastewater Infrastructure Scenarios in the San Diego‐Tijuana (US/MX) Border Region. (11th November 2021) - Feddersen, Falk; Boehm, Alexandria B.; Giddings, Sarah N.; Wu, Xiaodong; Liden, Doug
Abstract: The popular beaches of the San Diego‐Tijuana (US/MX) border region are often impacted by untreated wastewater sourced from Mexico—via the Tijuana River Estuary (TJRE) and San Antonio de los Buenos outfall at the Pt. Bandera (SAB/PTB) shoreline, leading to impacted beaches and human illness. The US‐Mexico‐Canada trade agreement will fund border infrastructure projects reducing untreated wastewater discharges. However, estimating project benefits such as reduced human illness and beach impacts is challenging. We develop a coupled hydrodynamic, norovirus (NoV) pathogen, and swimmer illness risk model with the wastewater sources for the year 2017. The model is used to evaluate the reduction in human illness and beach impacts under baseline conditions and three infrastructure diversion scenarios which (Scenario A) reduce SAB/PTB discharges and moderately reduce TJRE inflows or (Scenarios B, C) strongly reduce TJRE in inflows only. The model estimates shoreline untreated wastewater and NoV concentrations, and the number of NoV ill swimmers at Imperial Beach CA. In the Baseline, the percentage of swimmers becoming ill is 3.8% over 2017, increasing to 4.5% during the tourist season (Memorial to Labor Day) due to south‐swell driven SAB/PTB plumes. Overall, Scenario A provides the largest reduction in ill swimmers and beach impacts for the tourist season and full year. The 2017 tourist season TJRE inflows were not representative of those in 2020, yet, Scenario A likely still provides the greatest benefit in other years. This methodology can be applied to other coastal regions with wastewater inputs. Plain Language Summary: The popular beaches of the San Diego‐Tijuana border region are often impacted by Mexican‐sourced untreated wastewater leading to beach advisories and human health impacts. There are two principal ocean sources: the Tijuana River Estuary (TJRE) and San Antonio de los Buenos outfall at Pt. Bandera (SAB/PTB). The recent US‐Mexico‐Canada trade agreement will fund infrastructure projects to reduce untreated wastewater flowing into the ocean. Estimating project benefits requires coupling models, which is challenging and has not previously been performed. We develop such a model to estimate shoreline pathogen concentration and swimmer illness risk for the year 2017 for four scenarios of baseline conditions and three infrastructure diversion scenarios which (Scenario A) reduce SAB/PTB discharges and moderately reduce TJRE inflows or (Scenarios B, C) strongly reduce TJRE inflows only. In the Baseline, the percentage of swimmers becoming ill is 3.8% over the year, increasing to 4.5% for the tourist season (Memorial to Labor Day) due to south‐swell driven SAB/PTB plumes. Overall, Scenario A provides the largest reduction in ill swimmers both for the tourist season and full year relative to Scenarios B and C that only reduce TJRE inflows. This methodology can be applied to other regions where wastewater enters the ocean. Key Points: We develop a coupled hydrodynamic, a pathogen, and swimmer illness model to evaluate US/MX border region shoreline wastewater impacts Year 2017 model simulations quantitatively assess the benefits of four infrastructure scenarios that reduce regional wastewater inputs Tourist season has the most ill swimmers from plumes advecting north from MX, and mitigating this source yields the largest benefit